The value of dog for knowledge of human Duchenne muscular dystrophy: New findings in pathogenesis and therapeutic advances - de Moraes, Julieta R. Engrácia [UNESP]; Malvestio, Lygia M. [UNESP]; Martins, Isabela M. [UNESP]; de Moraes, Flávio Ruas [UNESP] (My University, 2015)
Duchenne muscular dystrophy (DMD) is the most devastating form of inherited muscular dystrophy in men. The loss of dystrophin causes progressive weakness and degeneration of skeletal and cardiac muscle leading to the replacement of muscle by connective tissue and fat in an X-linked recessive disorder. The onset of the disease occurs between 2 and 5 years of age and many patients die from cardiac or respiratory failure. The canine model Golden Retriever with muscular dystrophy (GRMD) is the most appropriate experimental model to study the disease because the development of muscular alterations and clinical course are strikingly similar to those described for human condition and thus very useful for the effectiveness of the treatment trials. Several studies have been performed in GRMD to show possible mechanisms responsible for degeneration and cell death and evaluate potential treatments to minimize disease severity and improve life expectancy in human DMD. This chapter presents an overview on the relevant contribution of canine model GRMD to better knowledge of human DMD.
Keywords: Canine model GRMD; DMD like; Duchenne; GRMD; Muscular dystrophy